Classical Services Using HOTS-Based Interactive Multimedia for Fifth-Grader of Elementary School - Desy Irsalina Savitri; Kartini Kartini; Mety Toding Bua; Jhoni Eppendi; Nindya Adiasty; Dian Fitri Nur'aini (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2023)
This research was initiated by the insufficient learning media used in the classical service process applied by teachers. Teachers should implement classical services since students are taking formal education in elementary schools as the right way to start using HOTS-based learning, which will develop students’ critical thinking skills. The learning media will assist the teacher in optimizing potential achievement. The interactive multimedia combines audio and visual media to help students use learning technology 4.0, think critically, and increase student interest in the learning process. This study was a descriptive quantitative method to describe the feasibility results of HOTS-based learning media. The criteria for multimedia eligibility level was around 81-100%, which is a very feasible criterion. This data was obtained from a questionnaire through Google Forms. The feasibility questionnaire analysis defined that the media is feasible to use, where the teachers' response was 87.6%, and the students were 87.3%.